A Fuzzy adaptive hysteresis band controller for three phase four wire UPQC - Shamshul Haq, S; Lenine, D; V. N. L. Lalitha, S (International Journal of Engineering and Technology, 2018)
Unified Power Quality Compensator (UPQC) is used to protect the sensitive loads in the distribution system from voltage and current disturbances. The compensation capability of UPQC depends on the control strategies used for shunt and series converters. Conventional adaptive hysteresis controller pulse width modulation technique had failed to track exactly during transient conditions and disturbances at load and source side. In paper fuzzy adaptive hysteresis controller is proposed for three phase four wire UPQC for compensating voltage sag/swell, current harmonics, voltage harmonics and neutral current compensation. Fuzzy adaptive hysteresis controller can effectively compensate the power quality problems during the transient conditions. A comparative simulation analysis of proposed and conventional methods are presentedÂ Â  in this paper using MATLAB/SIMULINK tool.